Early Effects of Intensive Lipid-Lowering Treatment on Plaque Characteristics Assessed by Virtual Histology Intravascular Ultrasound - Lee, Jung-Hee; Shin, Dong-Ho; Kim, Byeong-Keuk; Ko, Young-Guk; Choi, Donghoon; Jang, Yangsoo; Hong, Myeong-Ki (Yonsei medical journal, 2016)
The effects of short-term intensive lipid-lowering treatment on coronary plaque composition have not yet been sufficiently evaluated. We investigated the influence of short-term intensive lipid-lowering treatment on quantitative and qualitative changes in plaque components of non-culprit lesions in patients with acute coronary syndrome. This was a prospective, randomized, open-label, single-center trial. Seventy patients who underwent both baseline and three-month follow-up virtual histology intravascular ultrasound were randomly assigned to either an intensive lipid-lowering treatment group (ezetimibe/simvastatin 10/40 mg, n=34) or a control statin treatment group (pravastatin 20 mg, n=36). Using virtual histology intravascular ultrasound, plaque was characterized as fibrous, fibro-fatty, dense calcium, or necrotic core. Changes in plaque components during the three-month lipid-lowering treatment were compared between the two groups. Compared with the control statin treatment group, there was a significant reduction in low-density lipoprotein cholesterol in the intensive lipid-lowering treatment group (-20.4±17.1 mg/dL vs. -36.8±17.4 mg/dL, respectively; p<0.001). There were no statistically significant differences in baseline, three-month follow-up, or serial changes of gray-scale intravascular ultrasound parameters between the two groups. The absolute volume of fibro-fatty plaque was significantly reduced in the intensive lipid-lowering treatment group compared with the control group (-1.5±3.4 mm³ vs. 0.8±4.7 mm³, respectively; p=0.024). A linear correlation was found between changes in low-density lipoprotein cholesterol levels and changes in the absolute volumes of fibro-fatty plaque (p<0.001, R²=0.209). Modification of coronary plaque may be attainable after only three months of intensive lipid-lowering treatment.